First-In-Human Study to Assess the Safety, Pharmacokinetics, and Pharmacodynamics of SHR2285, a Small-Molecule Factor XIa Inhibitor in Healthy Subjects - Chen, Rui; Guan, Xiaoduo; Hu, Pei; Dong, Yanli; Zhu, Yi; Zhang, Tengfei; Zou, Jianjun; Zhang, Shuyang (Frontiers in Pharmacology, 2022)
Background: Targeting factor XI (FXI) is a promising therapeutic strategy for the treatment and prevention of thrombosis without increasing the risk of bleeding. Here, we assessed the safety, pharmacokinetics (PK), and pharmacodynamics (PD) of SHR2285, a novel FXIa inhibitor, in healthy subjects. Methods: In this randomized, double-blinded, placebo-controlled, dose-ascending single-dosing trial (NCT03769831), eligible volunteer subjects receive either SHR2285 or placebo in a 3:1 ratio. Subjects assigned to the SHR2285 group received a single oral dose of SHR2285 at 50 mg, which was subsequently escalated to 100 mg, 200 mg, and 400 mg. Safety, pharmacokinetics, and pharmacodynamics parameters were assessed. All subjects were followed for 6 days. Results: SHR2285 was well tolerated. All adverse events were grade 1, and there was no evidence of bleeding events. The PK results revealed a rapid onset of action of SHR2285 (median time to maximum plasma concentration [Tmax] in different dose groups ranged 3.0–4.0 h) and the mean half-life ranged from 7.6 to 15.8 h. The metabolite SHR164471 had a slightly longer Tmax than the parent SHR2285, reaching a peak at a median of 6.0–7.0 h, and its mean half-life were 10.1–14.7 h in different dose groups. The sums of the area under the concentration–time curve from zero to time infinity of SHR2285 and SHR164471 in the 200 and 400 mg groups were similar, indicating the sum pharmacological activity of SHR2285 and SHR164471 showed a saturation trend between 200 and 400 mg. PD analysis showed that the inhibition of FXI activity was synchronized with prolonged activated partial thromboplastin time after SHR2285 administration, but the serum prothrombin time and international normalized ratio levels were not affected by SHR2285. Conclusion: SHR2285 demonstrated favorable safety, PK, and PD profiles in the dose range of 50 mg–400 mg. This first-in-human study supports the further development of SHR2285 for indications requiring anticoagulation. Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT03769831, identifier [NCT03769831].